Formulation, Development and Evaluation of Bisoprolol Sustained Release Tablets - Masum, M.; Ripon, M. A. R.; Bhowmik, D. R.; Amin, M. T.; Arefin, S.; Hossain, M. S. (Journal of Scientific Research, 2021)
Bisoprolol is a type of antihypertensive drug (β-blocker). It is a poorly water-soluble and highly permeable drug that belongs to class II biopharmaceutical classification. This investigation represents the formulation development of bisoprolol to sustain the drug release. Different types of polymers like hypromellose, xanthan gum, avicel, poly ethylene glycol (PEG) were used in this study. Three different formulations were developed by using different excipients at various ratios. The granules were evaluated for bulk density, tapped density, flow property whereas tablets were evaluated for thickness, hardness, weight variation, compressibility index, uniformity of content, disintegration time, and drug release profile. The concentration of the diffused drug was measured using a UV-visible spectrophotometer at λmax= 225 nm. Granules showed good flow ability and all the formulations passed the quality. Among all the formulations, F-2 and F-3 showed better efficiency. PEG along with hypermellose, and guar gum showed a good combination for sustaining the drug release